Optimal discounts in Green Public Procurement - Olga Chiappinelli; Gyula Seres (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
We consider a Green Public Procurement setting where the procurer provides a bid discount to environment-friendly technologies to foster their use. We assume that, before the auction, firms may switch to green technology via a publicly observable costly investment. We show that investment acts as a signaling device. This mitigates the effect of incomplete information on firms' costs, thereby triggering more competitive bidding, which results in lower prices for the procurer. Therefore, even a procurer with no preference toward green technology can find it optimal to use a discount. Our results challenge the common perception that Green Public Procurement always implies a trade-off between environmental performance and purchasing price.
Keywords: D44; H57; Q58; Q55; 330; Public Procurement; Environmental Policy; Auctions